2017
DOI: 10.1515/jwld-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

The quality of surface waters of the dam reservoir Mexa, Northeast of Algeria

Abstract: In this work, we have conducted a physicochemical study that assesses the impact of agricultural activities and urban domestic wastewater on the surface water quality of the dam reservoir Mexa in the area of El-Taref, which is located in the eastern coastal basin of Constantine. 36 samplings have been conducted for three years (2010, 2011 and 2012), at the rate of one sampling per month on the dam reservoir water; 36 samples have been analysed. The samples taken have been subjected to an in situ measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
3
10
0
Order By: Relevance
“…Moreover, disinfection processes of water can result in higher pH values, while corrosion can drop the values into the acidic range ( Trivedi et al, 2009 ). Similar results, in this study, of iron (Fe), sulfate (SO 4 ), and Nitrite (NO 2 ) were obtained by Gulumbe ( Gulumbe et al, 2016 ) in Aliero dam water in Nigeria, and also by Bahroun & Chaib ( Bahroun and Chaib, 2017 ) in dam reservoir Mexa in the northeast of Algeria. Regarding nitrate level, the results of this work are in agreement with those obtained by Abdelali who found that all values of NO 2 in Beyler Dam Lake were below the permitted levels of the surface water quality regulations ( Abdelali et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, disinfection processes of water can result in higher pH values, while corrosion can drop the values into the acidic range ( Trivedi et al, 2009 ). Similar results, in this study, of iron (Fe), sulfate (SO 4 ), and Nitrite (NO 2 ) were obtained by Gulumbe ( Gulumbe et al, 2016 ) in Aliero dam water in Nigeria, and also by Bahroun & Chaib ( Bahroun and Chaib, 2017 ) in dam reservoir Mexa in the northeast of Algeria. Regarding nitrate level, the results of this work are in agreement with those obtained by Abdelali who found that all values of NO 2 in Beyler Dam Lake were below the permitted levels of the surface water quality regulations ( Abdelali et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…The largest difference between stations was observed in spring for P-PO 4 , and it was 13.1 mg/dm 3 . Similar dependence was observed for N-NO 3 , the difference was 13.2 mg•dm 3 .…”
Section: Soil Examinations On Samples From the Drainage Areasupporting
confidence: 82%
“…In summer, however, significant drop in O 2 content was observed. Drop in oxygen content in lakes at this time of year is connected with increase in the content of P-PO 4 and P tot [3,25], which is evidenced by P-PO 4 contents in Lake Czolnowskie in summer. Furthermore, in summer aquatic plants decompose and later the dead matter is deposited at the bottom, thus reducing the oxygen content in water [26].…”
Section: Lake Surface Watersmentioning
confidence: 81%
See 1 more Smart Citation
“…Water is the most essential supporting element for the survival of human life, gives full support in the movement, circulation and cycling of nutrients [BANO 2017;DAHOUA et al 2017;HAMAD et al 2018b]. In the last few decades, there has been a tremendous increase in the demand for fresh water due to rapid growth of population, unplanned urbanization, industrialization and too much use of fertilizers and pesticides in agriculture [BAHROUN, CHAIB 2017;BESSER et al 2018;HAMED et al 2018;JOARDER et al 2008]. Meanwhile sufficient potable quality of water is deteriorating and its pollution level is going up at a fast rate.…”
Section: Introductionmentioning
confidence: 99%